Instytucje rynkowe w Polsce a proces integracji w Unii Europejskiej (na przykładzie giełd towarowych) - Drewiński, Marek (Market Institutions in Poland and Integration's Process in the European Union (the Example of Commodity Exchange), 2007)
The paper brings closer the process of setting up and evaluation of commodity and wholesale markets, contributing to the process of transformation of Polish economy after 1990. The most important conditions of this process and the importance of established trade for functioning and development of food and agricultural market in Poland were shown. The impact of government institutions and social organizations was evaluated in the paper. Legal and financial regulations were assesed too. In the conclusion the alternative scenarios of the development of commodity markets in Poland were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 74-85